Analysis of errors in writing letters of the alphabet among female employees at Imam Shafi’i College in Jember - Nurhibbulwalidain, Nurhibbulwalidain; Juhari, Imam Bonjol; Maulana, Asep (Abjadia : International Journal of Education, 2025)
This research aimed to identify errors in writing alphabets among female employees at Imam Shafi'i College in Jember. The research relied on the descriptive approach, and the researcher relies on collecting data on observation, and answer sheets, where the researcher developed limited written test questions from some alphabets for eight female employees at Imam Shafi'i College in Jember and the researcher used data analysis from Miles and Hubermen. Error analysis is applied linguistics, and this research focuses on calligraphy or is called drawing letters. The researcher is looking for writing errors in drawing the alphabets and the researcher's choice of the unique research object, and they are the employees of Imam Shafi'i College in Jember, where most of them are beginners and housewives and feel difficult to write the alphabet well. The researcher found some errors in their writing and need to be analyzed. The results of the research that the forms of errors are of three types, namely drawing letters not connected to what came before and after, error in setting the point and avoiding the learner rule in drawing letters. The reasons for errors in drawing alphabets are ignorance of the rule, lack of training and lack of concentration.